SOME FORMS OF RECEPTION OF CICERO IN THE TEXTBOOK ON ELOQUENCE “THE MOHYLA SPEAKER” (1636) - Olga Zyganok; Valentyna Halagan (Lìteraturnij Proces: Metodologìâ, Ìmena, Tendencìï)
The article analyses some forms of Mark Tullius Cicero’s reception in the earliest textbook on the rhetoric of the Kyiv-Mohyla Academy — “Orator Mohileanus” (1636) by Joseph Kononovich-Gorbatsky. The author of the national course in various ways indicates that he builds his course on the teachings of the father of eloquence, which he considers «Ours». Cicero for the Kyiv teacher is an absolute authority, not only as an orator and teacher of eloquence, but also as a politician and personality. However, we come across both the protection of the Roman speaker against possible opponents, and the elements of discussion with the Roman master. Joseph Kononovich-Gorbatsky considers the treatise “Of the Classification of Rhetoric” as a very good example of the short rhetorical teaching to beginners, in his case, to the students whom he calls Cicero candidates. The Roman coryphaeus is often paired with other authors in the Ukrainian textbook, most often with Quintilian. The textbook “Orator Mohileanus” is rich in definition, demonstrating a great variety in form. Cicero’s terminology is widely used in the Ukrainian manual, although it is not fully elaborated but sometimes controversial. Josip Kononovich-Gorbatsky uses different ways of commenting: explaining the term of Cicero, explaining his thoughts, etc. Sometimes the Ukrainian author is not sure that he well understood the Cicero’s idea. There are many examples of Cicero in Ukrainian rhetoric. The quotations are made in several forms: quotation of several fragments of Cicero’s works, a fragment or just the beginning.